2011
DOI: 10.1590/s1808-86942011000400013
|View full text |Cite
|
Sign up to set email alerts
|

Computerized analysis of snoring in sleep apnea syndrome

Abstract: The International Classification of Sleep Disorders lists 90 disorders. Manifestations, such as snoring, are important signs in the diagnosis of the Obstructive Sleep Apnea Syndrome; they are also socially undesirable.Objective: The aim of this paper was to present and evaluate a computerized tool that automatically identifies snoring and highlights the importance of establishing the duration of each snoring event in OSA patients. Material and Methods:The low-sampling (200 Hz) electrical signal that indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…The les were records taken every 600 s. Dominant frequencies for each 0.01-s segment were analyzed and plotted. Simultaneously, Hilbert amplitude envelopes were smoothed using a sample-moving average of 1000 samples with a 25% overlapping sliding window [9,10,19,20]. Visualization revealed that the clustered snores in the amplitude domains generally exhibited nearisometric spikes with a trend of initial ascension and subsequent descension.…”
Section: Snoring Rates Obtained Using Our Dependable Algorithmmentioning
confidence: 99%
“…The les were records taken every 600 s. Dominant frequencies for each 0.01-s segment were analyzed and plotted. Simultaneously, Hilbert amplitude envelopes were smoothed using a sample-moving average of 1000 samples with a 25% overlapping sliding window [9,10,19,20]. Visualization revealed that the clustered snores in the amplitude domains generally exhibited nearisometric spikes with a trend of initial ascension and subsequent descension.…”
Section: Snoring Rates Obtained Using Our Dependable Algorithmmentioning
confidence: 99%
“…Embletta MPR microphone (an analog omnidirectional condenser microphone) attached to nasal cannula will record the snoring sounds. All signals will be fed into analog/digital (A/D) converter with a 200 Hz sampling rate (each channel has 200 points or samples per second; Shiomi et al, 2011 ). For optimal visualization of snoring, a high-pass filter to remove very low frequencies (20 Hz) and a low-pass filter to remove high frequencies (3 kHz) will be used, this will permit acquiring relevant information of snoring sounds (Pevernagie et al, 2010 ).…”
Section: Outcome Measurements and Stepwise Proceduresmentioning
confidence: 99%
“…In addition, it records how much air moves in and out of the lungs during sleep and the amount of oxygen in the blood [10,11]. It records what happens with breathing during sleeping.…”
Section: Introductionmentioning
confidence: 99%